3D Game-Based Learning Media Using a Deep Learning Approach to Enhance Understanding of Natural and Social Science (IPAS) Concepts - Ni Nengah Sari Jati; I Nyoman Laba Jayanta; I Made Hendra Sukmayasa (Universitas Pendidikan Ganesha, 2026)
The low level of students’ understanding of the IPAS concept, caused by insufficiently interactive learning and minimal use of digital media, forms the background of this study. This study aims to develop and test the feasibility of a 3D game-based learning medium using a deep learning approach for food chain material. This study employs a research and development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects included subject matter experts, media experts, teachers, and elementary school students. Data collection techniques included observation, interviews, questionnaires, and tests, with instruments such as expert validation sheets, practicality questionnaires, and pretest and posttest questions. Data were analyzed using quantitative descriptive analysis and a paired-sample t-test. The results of the study indicate that the developed media possess a very high level of validity, excellent practicality, and are effective in significantly improving students’ conceptual understanding. The use of 3D game-based media utilizing deep learning is capable of fostering active student engagement and facilitating meaningful learning. Thus, the developed media have the potential to serve as an innovative alternative for enhancing the quality of IPAS learning in elementary schools.